Hydrogels as Soft Ionic Conductors in Flexible and Wearable Triboelectric Nanogenerators. Issue 11 (20th February 2022) - Wu, Yinghong; Luo, Yang; Cuthbert, Tyler J.; Shokurov, Alexander V.; Chu, Paul K.; Feng, Shien‐Ping; Menon, Carlo
Abstract: Flexible triboelectric nanogenerators (TENGs) have attracted increasing interest since their advent in 2012. In comparison with other flexible electrodes, hydrogels possess transparency, stretchability, biocompatibility, and tunable ionic conductivity, which together provide great potential as current collectors in TENGs for wearable applications. The development of hydrogel‐based TENGs (H‐TENGs) is currently a burgeoning field but research efforts have lagged behind those of other common flexible TENGs. In order to spur research and development of this important area, a comprehensive review that summarizes recent advances and challenges of H‐TENGs will be very useful to researchers and engineers in this emerging field. Herein, the advantages and types of hydrogels as soft ionic conductors in TENGs are presented, followed by detailed descriptions of the advanced functions, enhanced output performance, as well as flexible and wearable applications of H‐TENGs. Finally, the challenges and prospects of H‐TENGs are discussed. Abstract : Owing to its stretchability, biocompatibility, and tunable ionic conductivity, hydrogels have gained increasing attention as current collectors in triboelectric nanogenerators (TENGs). However, a comprehensive review concerning the development of hydrogel‐based TENGs (H‐TENGs) is still lacking. This paper summarizes the recent progress and prospect of H‐TENGs for flexible and wearable applications. Challenges and opportunities of this exciting area are highlighted.